Stress exacerbates DNCB-induced atopic dermatitis in BALB/c mice: association with modulation of the gut microbiome - So Min Lee; Keun Hyang Eom; Jeeyoun Jung; Jun-Chul Kang; Jae-Sang Ryu; You Mee Ahn; Ji-Yeun Park (Stress)
Atopic dermatitis (AD) is a widely recognized chronic inflammatory skin disease influenced by dietary habits, stress, genetic factors, and environmental factors. This study aimed to explore the impact of stress on AD exacerbation, as well as the associated changes in the gut microbiota. We utilized a 2,4-dinitrochlorobenzene (DNCB)-induced AD mouse model subjected to chronic restraint stress (CRS). The animals were divided into four groups: normal, sham control (sham), AD, and AD+CRS. Scratching behavior was significantly increased in the AD+CRS group compared to the AD group on day 28, indicating that stress exacerbates pruritus in AD. Relative abundance analysis of the gut microbiota at the phylum level revealed an increased relative abundance of Bacteroidota in both the AD and AD+CRS groups. Principal coordinate analysis revealed distinct patterns between the AD and AD+CRS groups. The relative abundance of Heminiphilus was negatively correlated with immunoglobulin E (IgE) levels, while the relative abundance of Ruminococcus exhibited significant and negative correlations with both corticosterone and IgE levels. Alistipes, which is known to aggravate AD, was notably elevated in the AD+CRS group. These findings confirm that stress-related changes in the gut microbiota composition may contribute to the exacerbation of AD, highlighting the connection among stress, immune response, and microbiome dynamics in AD progression.